(untitled) (Journal of Nepal Physical Society, 2017)
Spin relaxation of muonium (Mu) observed in molecular oxygen (O2) dissolved in water shows characteristic behaviour which enables us to detect O2 in aqueous solution of albumin, serum and haemoglobin (Hb). These results suggest development of a new method using positive muon to measure oxygen level in biological systems which can be applied for diagnosis and treatment of cancer. Journal of Nepal Physical Society Volume 4, Issue 1, February 2017, Page: 7-10